2020
DOI: 10.1007/s11356-020-09607-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of SO2 and NOx sequential wet absorption in a two-stage bioscrubber for elemental sulphur valorisation

Abstract: Flue gases contain SO2 and NOx that can be treated together for elemental sulfur recovery in bioscrubbers, a technology that couples physical-chemical and biological processes for gaseous emissions treatment in a more economic manner than classical absorption. Sequential wet-absorption of SO2 and NOx from flue gas is thoroughly studied in this work in a two-stage bioscrubber towards elemental sulphur valorisation pursuing reuse of biological process effluents as absorbents. The optimal operating conditions req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…This is basically because NO is an acid gas, whereas the pH remained at 8 when phosphate solution was used due to its buffer potential effect. This is consistent with what was observed by Guimerà et al ( 2021 ), where no gas-to-liquid mass transfer was observed when a phosphate buffer was added in a system without NAP. However, the system was kept at a neutral pH.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is basically because NO is an acid gas, whereas the pH remained at 8 when phosphate solution was used due to its buffer potential effect. This is consistent with what was observed by Guimerà et al ( 2021 ), where no gas-to-liquid mass transfer was observed when a phosphate buffer was added in a system without NAP. However, the system was kept at a neutral pH.…”
Section: Resultssupporting
confidence: 93%
“…According to supplementary information Figure S 2 , the results confirmed that as soluble gases (NO 2 ) were formed in the gas phase, they were transferred to the liquid phase through different instantaneous and irreversible reactions with water or phosphate buffer to form nitrous and nitric acids as described by Guimerà et al ( 2021 ). The results of the mass transfer in the three-phase system (Figure S 2 ) showed a higher concentration of and in the aqueous phase when MTV was present compared to NAP-free blanks.…”
Section: Resultssupporting
confidence: 67%
“…Efforts have focused on the development of qualified technologies to eliminate SO 2 from coal-combustion flue gas. Flue-gas exhaust contains some CO, nitrogen oxides (NO X ), and small amounts of O 2 in addition to SO 2 [ 24 ]. Developing technologies for integrated methods of treating multiple greenhouse gases remains a global priority.…”
Section: Rss Definition and Relationship With Environmental Managementmentioning
confidence: 99%